2008
DOI: 10.1097/shk.0b013e31805cddce
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood-Derived Cd34+ Cells May Attenuate Spinal Cord Injury by Stimulating Vascular Endothelial and Neurotrophic Factors

Abstract: Human umbilical cord blood-derived CD34(+) cells were used to elucidate the mechanisms underlying the beneficial effects exerted by cord blood cells in spinal cord injury (SCI). Rats were divided into four groups: (1) sham operation (laminectomy only); (2) laminectomy + SCI + CD34(-) cells (5 x 10(5) human cord blood lymphocytes and monocytes that contained <0.2% CD34(+) cells); (3) laminectomy + SCI + CD34(+) cells (5 x 10(5) human cord blood lymphocytes and monocytes that contained approximately 95% CD34(+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 30 publications
0
39
0
2
Order By: Relevance
“…Our data demonstrated that the protective mechanisms of transplanted hUCBSCs are associated with continuous secretion of BDNF and GDNF in vivo of retina of optic nerve injury rats. Elevated levels of BDNF and GDNF by grafted stem cells may promote differentiation of the grafted cells into neural cells, inhibit apoptosis, improve angiogenesis, suppress an inflammatory infiltrate, and maintain grafted cell survival [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that the protective mechanisms of transplanted hUCBSCs are associated with continuous secretion of BDNF and GDNF in vivo of retina of optic nerve injury rats. Elevated levels of BDNF and GDNF by grafted stem cells may promote differentiation of the grafted cells into neural cells, inhibit apoptosis, improve angiogenesis, suppress an inflammatory infiltrate, and maintain grafted cell survival [31].…”
Section: Discussionmentioning
confidence: 99%
“…Kao et al reported that systemic administration of 95% pure CD34þ progenitor cells derived from UCBSCs attenuates spinal cord infarction and apoptosis as well as behavioral deficits in a standard rat compression SCI model. In addition, current investigation provides new evidence suggesting that CD34þ cell therapy may cause restoration of spinal cord function during SCI by stimulating both GDNF and VEGF production in injured spinal cords (Kao et al, 2008). In previous reported clinical use of UCBSC to treat a patients with a SCI , it was stated that transplantation of UCBSCs improved sensory perception and mobility in hip and thigh regions.…”
Section: Non-embryonic Stem Cellsmentioning
confidence: 99%
“…There have been an increasing number of studies suggesting that these hUCB derived-CD34 + cells can induce angiogenesis and endo/exogenous neurogenesis in stroke (Taguchi et al, 2004) and SCI (Kao et al, 2008). In addition, Chen et al (2008) recently showed that hUCB cells have the ability to secrete multiple neurotrophic factors.…”
Section: Wwwintechopencommentioning
confidence: 99%